Comparative Effect of Calcium Phosphate Biocomposite Materials on the Healing of Experimental Defect of Compact Bone Tissue - Korenkov, Oleksii (Journal of Morphological Sciences, 2019)
Introduction For the treatment of bone defects, a considerably large number of biocomposite calcium-phosphate materials has been developed and used. However, in the scientific literature, there is no information about the comparative effect of biocomposite materials based on β-tricalcium phosphate, hydroxyapatite, and collagen on the dynamics of healing of the defect of compact bone tissue.Materials and Methods The experiment was performed on 48 white Wistar rats. In the middle third of the femoral shaft, a perforated defect 2.5 mm in diameter was reproduced in the bone marrow canal, which was filled with the calcium phosphate material Collapan (Intermedapatit, Moscow, Russia) (hydroxyapatite/collagen/antibiotics) in the animals of the first group, and with Guidor easy-graft Crystal (Sunstar S.A., Etoy, Switzerland) (hydroxyapatite/β-tricalcium phosphate) in the animals of the second group. Fragments of the injured bones were examined on the 15th and 30th days by light microscopy with morphometry and scanning electron microscopy.Results It was found that, in the area of implantation of Collapan and of Guidor easy-graft Crystal, signs of inflammation were not detected, and osteogenic cells exhibited high topism to biocomposite materials. The biomaterials during the entire period of the experiment are subjected to resorption and replacement by the bone tissue of the regenerate. On the 15th and 30th days of the experiment, the predominance in the rate of biomaterial resorption (of 35.04% and 53.47%, respectively) and the formation of regenerate bone tissue (of 58.67% and 50.47%, respectively) was in the area of implantation of Collapan.Conclusion The biocomposite materials tested exhibit a high biocompatibility, osteoconductive properties, and good integration with the tissues of the regenerate. However, the biocomposite material Collapan undergoes resorption and replacement by the bone tissue of the regenerate much faster, and Guidor easy-graft Crystal provides stability of the defect volume of compact bone tissue due to full resorption and good integration with the tissues of the regenerate.
Keywords: rats; reparative osteogenesis; β-tricalcium phosphate; hydroxyapatite; collagen